Cross-species screening of microsatellite markers for individual identification of snow petrel Pagodroma nivea and Wilson's storm petrel Oceanites oceanicus in Antarctica - Anant Pande; Nidhi Rawat; Kuppusamy Sivakumar; Sambandam Sathyakumar; Vinod B. Mathur; Samrat Mondol (PeerJ, 2018)
Seabirds are important indicators of marine ecosystem health. Species within the order Procellariiformes are the most abundant seabird species group distributed from warm tropical to cold temperate regions including Antarctica. There is a paucity of information on basic biology of the pelagic seabird species nesting on the Antarctic continents, and long-term studies are required to gather data on their population demography, genetics and other ecological parameters. Under the ‘Biology and Environmental Sciences’ component of the Indian Antarctic programme, long-term monitoring of Antarctic biodiversity is being conducted. In this paper, we describe results of cross-species screening of a panel of 12 and 10 microsatellite markers in two relatively little studied seabird species in Antarctica, the snow petrel Pagodroma nivea and the Wilson's storm petrel Oceanites oceanicus, respectively. These loci showed high amplification success and moderate levels of polymorphism in snow petrel (mean no. of alleles 7.08 ± 3.01 and mean observed heterozygosity 0.35 ± 0.23), but low polymorphism in Wilson's storm petrel (mean no. of alleles 3.9 ± 1.3 and mean observed heterozygosity 0.28 ± 0.18). The results demonstrate that these panels can unambiguously identify individuals of both species (cumulative PIDsibs for snow petrel is 3.7 × 10−03 and Wilson's storm petrel is 1.9 × 10−02) from field-collected samples. This work forms a baseline for undertaking long-term genetic research of these Antarctic seabird species and provides critical insights into their population genetics.